Effects of tumor staging and treatment modality on functional outcome and quality of life after treatment for laryngeal cancer. Issue 12 (9th March 2013) - Robertson, Stuart M.; Yeo, Justin C. L.; Sabey, Lesley; Young, David; MacKenzie, Kenneth
<x xml:space="preserve">Abstract</x> Background An earlier stage of primary disease at diagnosis is associated with better survival from laryngeal cancer. It remains unproven whether earlier stage is also associated with improved end‐organ function and quality of life after treatment. Methods Questionnaire packs were posted to 250 patients with laryngeal cancer treated between January 2006 and December 2008 within the West of Scotland. Packs contained the Voice Symptom Scale (VoiSS), MD Anderson Dysphagia Inventory (MDADI), and University of Washington Quality of Life Questionnaire (UW‐QOL). Results One hundred forty‐seven eligible patients provided data for analysis (59% of original cohort). Patients with an earlier stage of primary disease reported significantly better VoiSS, MDADI, and UW‐QOL scores (p < .05). No differences were found between scores of patients with T1 laryngeal disease treated with endoscopic laser resection (ELR) and radiotherapy. Conclusion An earlier stage at diagnosis is associated with significantly better end‐organ function and quality of life after treatment for laryngeal cancer. © 2013 Wiley Periodicals, Inc. Head Neck 35: 1759–1763, 2013